Veronicas and Carolinas:: Claim and struggles for life in pandemic times - Santos Oliveira, Everaldo (2022)
This text aims to reflect on the reality of impoverished black women, mothers of family, residents of “tenements” and urban squatters in downtown São Paulo, Brazil, and on how these women experience the impact of the challenges brought by the pandemic of Covid-19. Living in contexts already marked by many inequalities and violence, many of them structural, such as racism and gender inequalities, these women resist and try to build alternatives to survive with their families in a reality of insecurity and death. In the struggle for life, they reveal a painful face of God, who is present in their pain and suffering.